INTERNALISASI NILAI-NILAI KARAKTER PEDULI LINGKUNGAN DALAM MEMBENTUK PERILAKU BERSIH DI UPTD SMP NEGERI 1 PEMATANGSIANTAR - Monika Sinaga; Rina Devi Romauli Siahaan; Esra Delima Hutabarat; Cintya Lolita Hutabarat; Vercelly Hot Taruli Manik; Nova Carlina Hutahaean (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of internalizing environmental care character values ​​in shaping students' clean behavior at the UPTD of SMP Negeri 1 Pematangsiantar. The background of this study is based on the low consistency of clean behavior among students, even though the school has implemented various cleanliness programs. The approach used is descriptive qualitative, with data collection techniques in the form of observation and documentation carried out from August to December 2025. Data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the internalization of environmental care character values ​​takes place through three stages, namely value transformation through the delivery of moral messages and environmental literacy, value transactions through habituation activities such as daily duty, Clean Friday, and the LISA (See Trash Pick Up) movement, and transinternalization which is marked by the formation of students' clean behavior voluntarily without coercion. The success of value internalization is influenced by teacher role models, consistent habituation, and a school culture that supports clean behavior.